2019
DOI: 10.1186/s40645-019-0301-2
|View full text |Cite
|
Sign up to set email alerts
|

Some remarks on hydrogen-assisted electrical conductivity in olivine and other minerals

Abstract: Electrical conductivity in minerals is sensitive to hydrogen content, and therefore, it is a potentially important property from which one can infer hydrogen (water) distribution in the mantle. However, there has been much confusion in the reported results on hydrogen-assisted conductivity. In this paper, I review the existing experimental observations on hydrogenenhanced electrical conductivity in olivine and other minerals to identify the causes of confusion. Hydrogen loss as well as hydrogen gain could occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 96 publications
(192 reference statements)
2
17
0
Order By: Relevance
“…The EC of hydrated olivine single crystals along the three dominant crystallographic directions ([100], [010] and [001]) has been reported by Dai and Karato [35] under conditions of a broad temperature range of 573-1373 K at 4.0 GPa (Figure 7). In the low temperature range (573-900 K), the EC of olivine single crystal with a low ∆H (74 kJ/mol) shows a feeble anisotropy, which is in good agreement with previously obtained conductivity results [12,[93][94][95]. However, within the high temperature range (T > 1000 K), the EC of sample exhibiting a higher activation enthalpy (~130-150 kJ/mol) is obviously anisotropic, which is consistent with the results of high-temperature H-D inter-diffusion in olivine [96].…”
Section: Mineralsupporting
confidence: 91%
See 1 more Smart Citation
“…The EC of hydrated olivine single crystals along the three dominant crystallographic directions ([100], [010] and [001]) has been reported by Dai and Karato [35] under conditions of a broad temperature range of 573-1373 K at 4.0 GPa (Figure 7). In the low temperature range (573-900 K), the EC of olivine single crystal with a low ∆H (74 kJ/mol) shows a feeble anisotropy, which is in good agreement with previously obtained conductivity results [12,[93][94][95]. However, within the high temperature range (T > 1000 K), the EC of sample exhibiting a higher activation enthalpy (~130-150 kJ/mol) is obviously anisotropic, which is consistent with the results of high-temperature H-D inter-diffusion in olivine [96].…”
Section: Mineralsupporting
confidence: 91%
“…Opposed to the previous study, Karato [95,116] has proposed a theory to explain (a) the experimentally observed discrepancy of the activation enthalpies of electrical conductivity and diffusion in H-bearing olivine, and (b) the transition from isotropic behavior of olivine electrical conductivity observed at low-T to anisotropic one at high-T. According to this hybrid model, isotope diffusion coefficient is given by the harmonic mean of the different forms of hydrogen (free proton, one or two protons at M-site, etc.…”
Section: Some Remarks On the Evaluation Of The Electrical Conductivitmentioning
confidence: 73%
“…The above evaluation of C H2O variation relies on the extent of C H2O that can produce measurable changes in conductivity. This is unknown because both conductivity and C H2O are variables, and therefore insignificant dehydration during heating and H 2 O‐reaborption during cooling is still theoretically possible (Karato, 2019). In that case, the C H2O under higher‐temperature conditions for the ionic conduction regime would be slightly underestimated; namely, the conductivity is enhanced by less H 2 O, which further supports our conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…The impedance spectroscopy was made using the Solartron 1260 for the frequency range of 10 3 -10 6 Hz (we choose relative high-frequency range to minimize the water loss; see Karato, 2019) and the signal voltage is 1.0 V. In the impedance spectroscopy, we determine both the in-phase and outof-phase response of a sample to the applied AC voltage. Measuring both in-phase (real part of impedance [Z′]) and out-of-phase (imaginary part of impedance [Z″]) response is important because when conduction is due to migration of ions, migrating ions can be accumulated at the In most cases, the electrical conductivity of sample was acquired during the first cycle of decreasing temperature after the peak temperature was reached.…”
Section: 1029/2020jb020309mentioning
confidence: 99%